Developing secure web applications. (1st January 2012) - Choukse, Dharmendra; Kanellopoulos, Dimitris N.; Singh, Umesh Kumar
The security of web applications is an important issue for any organisation that deploys its own websites. If an organisation takes the required precautions and countermeasures, it can prevent the possible attacks. Otherwise, its critical data, reputation and credibility will be at risk. Nowadays, firewalls, intrusion detection systems (IDS) and intrusion prevention systems (IPS) provide security at the network layer. However, more than 70% of present world's security attacks exploit the vulnerabilities at the application level. Cross-site scripting, SQL injection, cookie poisoning and forceful browsing are some of the most common website vulnerabilities. Stringent user input validation, proper session management, and exploitation of web application firewalls, etc., can be used as countermeasures to combat the attacks on websites. In this paper, we discuss how attackers can exploit the vulnerabilities of web applications and how we can implement effective countermeasures to secure our web applications.